Inspirational Space as a Mechanism to Transform Departmental Culture - John Paxton (Academic Chairpersons Conference Proceedings, 2015)
Montana State University’s Computer Science Department created a collaborative, informal, Japanese-themed Student Success Center. The goal of the space was to broaden participation and induce cultural change in computer science. The design philosophy behind the room now serves as a model for collaborative space at MSU.
Keywords: Student Success; Inducing Culture Change